2023
DOI: 10.30656/ka.v5i1.5347
|View full text |Cite
|
Sign up to set email alerts
|

Empowering the Rural Communities through Education on the Use of Chrysanthemums as Medicinal Plants and Herbal Tea

Abstract: Chrysanthemum is widely known as ornamental plants, but chrysanthemums can also be used as medicinal plants and can be processed into healthy beverages known as chrysanthemum tea. The purpose of the PPM activity is to educate the community, especially PKK women who are participants in this activity about the role of chrysanthemum plants in the prevention and treatment of various diseases such as fever, hypertension, osteoporosis, eye healthy and making chrysanthemum tea as a healthy beverage. PPM activities wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The nutrient composition of the media meets appropriate standards for the growth of orchid explants from subcultures [13]. Using the combination of benzyl amino purine (BAP) with organic matter extract on VW media, showed that the average time of emergence of the fastest shoots was 13.3 DAP (Days after planting) [14].…”
Section: Bud Growing Time (Days) Number Of Shoots Shoot Lengthmentioning
confidence: 99%
See 3 more Smart Citations
“…The nutrient composition of the media meets appropriate standards for the growth of orchid explants from subcultures [13]. Using the combination of benzyl amino purine (BAP) with organic matter extract on VW media, showed that the average time of emergence of the fastest shoots was 13.3 DAP (Days after planting) [14].…”
Section: Bud Growing Time (Days) Number Of Shoots Shoot Lengthmentioning
confidence: 99%
“…Exogenous growth regulators are given to provide balance against endogenous hormones in order to be able to influence physiological responses as a driver of cell division and elongation during bud multiplication and bud morphogenesis [14]. Found that the combination of benzyl amino purine (BAP) with organic matter extract on VW media in BAP treatment 3 ppm + tomato extract showed the highest average number of shoots of 14 pieces, and in BAP treatment 2 ppm + tomato extract showed the highest average shoot length of 2.06 cm.…”
Section: Bud Growing Time (Days) Number Of Shoots Shoot Lengthmentioning
confidence: 99%
See 2 more Smart Citations